Transcription of subtelomerically located var gene variant in Plasmodium falciparum appears to require the truncation of an adjacent var gene. - Horrocks, P; Kyes, S; Pinches, R; Christodoulou, Z; Newbold, C (2004)
The Plasmodium falciparum R29 clone preferentially transcribes the R29var gene variant on rosette selection, unlike other isogenic clones from the same parasite lineage. Characterisation of the R29var gene locus revealed that this gene lies internal to, and is in a tail-to-tail orientation with, a second var gene variant (A4var) at one end of chromosome 13. In the R29 clone, a spontaneous deletion event between these two var variants deletes all of the A4var gene and the subtelomeric repetitive sequence arrays. We have previously shown that a simple disruption of the A4var gene is not sufficient to preferentially activate the R29var gene in rosette-selected parasites. We therefore hypothesised that the truncation of the chromosome end may be a key factor in predisposing the R29var variant to transcription under rosette selection conditions. Here, we have generated a panel of isogenic parasite clones with both intact and truncated A4var-R29var loci, and show that R29var transcription is only detected in rosette-selected clones with a truncated locus. Furthermore, we present provisional data describing the relative frequency with which this spontaneous deletion event occurs. These data have implications in our understanding of how spontaneous deletion events within subtelomeric var loci may affect transcription of these var gene variants.